The Role of Educational Leadership to Support National Resilience: An overview of Era 4.0 - Zakky Almubaroq, Hikmat; Komariah, Aan; C. Kurniatun, Taufani (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to create a model of educational leadership in the 4.0 era to support national resilience. The method used is research and development according to the 4-D model (define, design, develop, disseminate). Data are taken from online surveys in the form of questionnaires, educational leadership workshops, and focus group discussions. The educational leadership model to support national resilience, contains elements 1) Passion: love for the world of education; 2) Vision: end in mind or thinking from the end product; 3) Scenario skills: able to plan and anticipate; 4) Nationalism: understanding the history of civilisation and love cultural heritage; 5) Holistic, integral, comprehensive minded: broad-minded, interconnected and detailed; 6) Understanding the world of education: understanding the elements, components, and problems of education based on 3L: data literacy, technology literacy and human resources literacy; 7) Pancasila: understanding the values contained in each precept of Pancasila; 8) Prime concern for the public interest. This study contributes to the existing knowledge by providing useful insights on the role of educational leadership in era 4.0. Educational leadership 4.0 has played a great role in building national awareness of school citizens, forming a character that has a nationalism spirit and smartness in implementing the country’s foundation. Leaders become strategic forces transforming progress through school policies and culture.